2020
DOI: 10.1002/jcp.29469
|View full text |Cite
|
Sign up to set email alerts
|

CDC6 regulates both G2/M transition and metaphase‐to‐anaphase transition during the first meiosis of mouse oocytes

Abstract: Cell division cycle protein, CDC6, is essential for the initiation of DNA replication. CDC6 was recently shown to inhibit the microtubule‐organizing activity of the centrosome. Here, we show that CDC6 is localized to the spindle from pro‐metaphase I (MI) to MII stages of oocytes, and it plays important roles at two critical steps of oocyte meiotic maturation. CDC6 depletion facilitated the G2/M transition (germinal vesicle breakdown [GVBD]) through regulation of Cdh1 and cyclin B1 expression and CDK1 (CDC2) ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Therefore, CDC6 overexpression may promote the continuous G1/S phase transition, which can cause active proliferation of epithelial cells and even malignant transformation. Some studies have found that CDC6 is also involved in regulating s-G2/M checkpoint, coordinating the process from the S phase to the M phase, and preventing cells from entering the mitotic M phase before the completion of S- phase DNA replication [16,17]. Its expression requires strict regulation to ensure a normal cell cycle [3].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CDC6 overexpression may promote the continuous G1/S phase transition, which can cause active proliferation of epithelial cells and even malignant transformation. Some studies have found that CDC6 is also involved in regulating s-G2/M checkpoint, coordinating the process from the S phase to the M phase, and preventing cells from entering the mitotic M phase before the completion of S- phase DNA replication [16,17]. Its expression requires strict regulation to ensure a normal cell cycle [3].…”
Section: Discussionmentioning
confidence: 99%
“…By constructing a PPI network, a significant module that had a functional role in DNA replication and cell cycle regulation was identified. From the network, most of the top 10 hub genes identified ( CDK1, CCNA2, CCNB1, PLK1, CDC6 and AURKA ) were also associated with similar cell cycle regulatory functions [ 89 , 114 , 115 , 116 , 117 ]. This further reinforces the fundamental involvement of TTAGPs in cellular division.…”
Section: Discussionmentioning
confidence: 99%
“…We found that overexpression of Cdt1 leads to embryos arrest at zygotes stages, but the development with overexpressed MCM2 embryos is not affected, consistent with the expression patterns of Cdt1 and Mcm2 , revealing that CDT1 mainly regulates DNA replication as a regulator, while MCM2 is only involved in DNA replication as an ATPase. CDC6 has been shown to be involved in regulating meiosis in addition to being a subunit of PRC 13 . and CDT1 is involved in regulating kinetochore–microtubule attachments in mitosis 12 .…”
Section: Discussionmentioning
confidence: 99%